From Reception to Integration of Asylum Seekers and Refugees in Poland - Sobczak-Szelc, Karolina (Routledge Advances in European Politics, 2023)
This book sheds light on the complex experiences of asylum seekers and refugees in Poland, against a local backdrop of openly anti-refugee political narratives and strong opposition to sharing the responsibility for, and burden of, asylum seekers arriving in the EU. Through a multidimensional analysis, it highlights the processes of forced migrant admission, reception and integration in a key EU frontier country that has undergone a rapid migration status change from a transit to a host country. The book examines rich qualitative material drawn from interviews conducted with forced migrants with different legal statuses and with experts from public administration at the central and local levels, NGOs, and other institutions involved in migration governance in Poland. It discusses both opportunities for and limitations on forced migrants' adaptation in the social, economic, and political dimensions, as well as their access to healthcare, education, the labour market, and social assistance. This book will be of particular interest to scholars, students, policymakers, and practitioners in migration and asylum studies, social policy, public policy, international relations, EU studies/European integration, law, economics, and sociology.